Model konseling kelompok konstruktivistik - Indri Astuti (Ikatan Konselor Indonesia (IKI))
This research is aimed to observe the development to model of group counceling using a constructivist approach. The methodology of the research is employing Borg and Gall combined with the instructional design by Dick and Carey. The steps of the research include (1) preliminary research; (2) planning model development; (3) validation, evaluation and revision of model. The concept of instructional constructivist group counseling is intergrated between Gladding’s group counseling namely (1) beginning, (2) transition, (3) activity, (4) and termintion. Cognan’s (1) grouping, (2) situations, (3) intergrating, (4) questioning, (5) exhibition and reflection. This output of the research include instructional materials and student work sheet, group counseling guide and flowchard of constructivist group counseling.